1998
DOI: 10.1016/s0039-6028(98)00672-4
|View full text |Cite
|
Sign up to set email alerts
|

Probing the interface potential in stick/slip friction by a lateral force modulation technique

Abstract: The influence of the shape of the interaction potential is investigated on details in stick/slip friction as encountered between an AFM tip and a substrate. Based on qualitative arguments of stick/slip systems, a novel technique is introduced in which the AFM tip is brought into a lateral resonance mode. In comparison to a direct measurement in the stick/slip signal, we suggest that the method is preferable to highlight these non-linear characteristics. In combination with the shape of the surface potential in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…It has been known for several years that the actuation of the tip-sample contact by small oscillations reduces friction (Schimmel et al 1995;Dinelli et al 1997;Kerssemakers & Hosson 1998;Bureau et al 2000;Heuberger et al 2000;Riedo et al 2003). A recent study by Socoliuc et al (2006) demonstrates the possible efficiency of such an approach on the atomic scale elegantly.…”
Section: Atomic-scale Friction and The Prandtl-tomlinson Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been known for several years that the actuation of the tip-sample contact by small oscillations reduces friction (Schimmel et al 1995;Dinelli et al 1997;Kerssemakers & Hosson 1998;Bureau et al 2000;Heuberger et al 2000;Riedo et al 2003). A recent study by Socoliuc et al (2006) demonstrates the possible efficiency of such an approach on the atomic scale elegantly.…”
Section: Atomic-scale Friction and The Prandtl-tomlinson Modelmentioning
confidence: 99%
“…Since stick-slip movement has been identified as the underlying mechanism for atomic-scale friction, it would be of pre-eminent technological importance if strategies could be found that allow one to prevent or suppress this effect. It has been known for several years that the actuation of the tip-sample contact by small oscillations reduces friction (Schimmel et al 1995;Dinelli et al 1997;Kerssemakers & Hosson 1998;Bureau et al 2000;Heuberger et al 2000;Riedo et al 2003). A recent study by Socoliuc et al (2006) demonstrates the possible efficiency of such an approach on the atomic scale elegantly.…”
Section: Atomic and Friction Force Microscopymentioning
confidence: 99%
“…An analysis of this linear force is reported elsewhere [45]. A rigorous description of this process for a periodic surface motion yields a non-linear equation of motion and requires quantitative models of lateral contact mechanics of the tip surface junction [46][47][48][49][50]. Here, these effects will be addressed experimentally in section 5.…”
Section: Frictionless Contactmentioning
confidence: 99%
“…De Hosson(53) assessed slip/stick friction by laterally resonating the tip in close proximity to the surface. McKendry et al(54) examined chiral interactions using chemical force microscopy.…”
mentioning
confidence: 99%